(untitled) (Medico Legal Update, 2020)
Background/Objectives: The purpose of this study is to investigate how the communication training program effects on communication skills and empathy ability in dental hygiene students. Method/Statistical Analysis: 21 students who wanted to participate in the communication program and 23 students who did not want to participate in the program were set as the control group. After implementing the communication program, we evaluated the improvement of communication skills and empathy before and after the program. The communication program consisted of 4 sessions (2-3 hours per session) Findings: Unlike the control group, the experimental group showed statistically significant effect of the program in both communication ability and empathy ability. Dental hygiene students have a good understanding other’s perspectives, while their ability to overcome stereotypical thinking and creative communication is low. Improvements/Applications: Communication program is effective in improving communication ability and empathy ability, so more detailed and specialized programs should be developed to cultivate communication skill and empathy ability.